Experience of Glatiramer Acetate in the Treatment of Relapsing-Remitting Multiple Sclerosis Patients - Özlem Taşkapılıoğlu (Türk Nöroloji Dergisi, 2012)
OBJECTIVE: Glatiramer acetate (GA) has been shown to reduce the number of relapses and improve outcomes in relapsing-remitting multiple sclerosis (RRMS) patients. The aim of this study is to investigate the efficacy and side effects of GA in RRMS patients treated with it. METHODS: We retrospectively reviewed all the records of RRMS patients treated with GA in our hospital from January 1990 to December 2010. We evaluated 114 records but 71 patients (48 women, 23 men) were included in the study due to incompleteness in the other records. Demographic characteristics, time from first symptom to diagnosis, time from diagnosis to treatment, number of relapses and Expanded Disability Status Scale (EDSS) scores before and after the treatment, treatment duration, side effects, the other agents used in MS treatment during the disease duration and the presence of oligoclonal bands were recorded. RESULTS: The mean age of the patients and mean GA treatment duration were 41,85±9,05 years and 28,73 months, respectively. The mean number of relapses before and after the treatment were 2.30±1.16 and 0,52±1.24 respectively. The number of relapses reduced in 64 (90,14%), unchanged in 4 (5,63%) and increased in 3 (4,23%) patients after GA treatment. The mean EDSS scores before and after the treatment were 2,56±1,46 and 2,04±1,68 respectively. Before GA treatment, 63,4% of all patients had EDSS scores three or more. After the treatment 50,6% of all patients had EDSS scores three or more. GA was the first choice immunomodulatory treatment in 71,8% and the second choice in 28,2% of the patients. The treatment discontinued in 8 (11,3%) patients and the reason was the severe side effect in only one patient (1,4%). CONCLUSION: Glatiramer acetate decreased the number of relapses and EDSS score with tolerable side effects